Pengaruh Media Kata Bergambar dalam Mengupayakan Kemampuan Pra-Membaca Permulaan pada Anak Kelompok B di TK Insan Cemerlang Kota Makassar - Wahyuna Wahyuna; Sri Sufliati Romba; Musfira Musfira (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The main problem in this study is how the influence of picture word media in pursuing the ability of early pre-reading in group B children in Insan Cemerlang Kindergarten, Makassar City. This study aims to find out how the influence of picture word media in pursuing the ability of early pre-reading in group B children in Kindergarten Insan Cemerlang Makassar City. The type of research used was an experiment using a one group pretest-posttest research design. The sample used was 14 students of class B2 of Insan Cemerlang Kindergarten. The instrument used to collect the data was a pre-reading developmental check technique. Data collection techniques through observation, interviews and documentation. The data analysis technique used was the Wilcoxon Signed Rank Test with the IBM SPSS 25 program. Based on the results of the study, it showed a significant influence on children's initial pre-reading ability after being treated in the form of picture word media. The average pre-test score is 5.5 while the average post-test score increases to 13. Based on the results of the analysis of the Wilcoxon Signed Rank Test data, the Asymp.sig (2-tailed) value of 0.01 indicates that the probability is below 0.05 (p<0.05). So Ho was rejected. Thus, the media of pictorial words has been proven to have a significant effect in overcoming the initial pre-reading ability of group B children at Insan Cemerlang Kindergarten in Makassar City. This research contributes to the development of effective learning methods to improve early pre-reading skills in early childhood